Well-being and Quality of Life Medical Perspective - Mollaoglu, Mukadder (IntechOpen, 2017)
The chapters in this book focus on the physical, social, and emotional components of the concept of quality of life. How diseases affect the quality of life of people is mainly discussed. The influence of diseases on quality of life in age-specific periods such as childhood, youth, and old age is also emphasized. In some non-disease-related environmental factors, specific social phenomena have also been analyzed. I hope that current research and research results in the book will be used to increase the quality of life by health professionals. This book will attract not only health workers but also environmentalists and social scientists and behavioral scientists.